An assessment of exposure to noise and temporary changes in hearing related to working as a fitness instructor - Anna Wolniakowska; Adam Dudarewicz; Kamil Zaborowski; Małgorzata Pawlaczyk-Łuszczyńska; Mariola Śliwińska-Kowalska (Nofer Institute of Occupational Medicine, 2021)
Background Music is for many people an integral part of their lives. In recent years, loud music, whether recorded or played live, has been a significant source of noise. The aim of the study was to assess the relationship between exposure to high sound levels and temporary threshold shift (TTS) in people working as fitness instructors. Material and Methods The study included a total of 29 people (26 women and 3 men, age: 33±6 years) employed in 8 fitness clubs. The sound levels and the frequency characteristics of noise were assessed using individual dosimetry. Hearing threshold was evaluated by pre- and post-exposure pure tone audiometry (PTA), yielding a total of 116 audiograms. Results Occupational exposure of fitness instructors to noise lasted 60-120 min and the A-weighted sound pressure level (L Aeq,T ) in their workplace ranged 76.3-96.0 dBA (M = 87.1 dB). In 12% of individual measurements, the maximum admissible intensity (MAI) value for noise at the workplace was exceeded (MAI = 85 dB). In 41% of the surveyed instructors, a TTS of ≥6 dB at 4 kHz was observed. Conclusions Fitness instructors may be a risk of hearing impairment related to their work. Med Pr. 2021;72(4):391-7